Gold Nanomaterials in Biosensing Applications - Zuo, Xinlin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
This paper provides an overview of the preparation and application of gold nanomaterials in biosensing, including four aspects: biomolecular detection, medical bioimaging, pathogen detection, and immunoassay. Firstly, the preparation methods of gold nanomaterials are introduced, including chemical reduction, laser radiation, and vacuum evaporation. Secondly, the applications of gold nanomaterials biosensors in various fields are outlined. One such field is biomolecule detection. gold nanomaterials has good optoelectronic properties, which can quantitatively detect biomolecules through fluorescence signals. Another field is medical bio-imaging. gold nanomaterials exhibits high X-ray absorption coefficients, rendering it a suitable contrast agent for medical imaging. Additionally, gold nanomaterials displays a high antigen-antibody reaction activity, making it an effective tool for rapid pathogen detection. Finally, the prospective development trend of gold nanomaterials biosensors is presented.